1989
DOI: 10.1002/j.1460-2075.1989.tb03439.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of tissue-specific alternative splicing: exon-specific cis-elements govern the splicing of leukocyte common antigen pre-mRNA.

Abstract: Tissue-specific alternative splicing is an important mechanism for controlling gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
99
3

Year Published

1990
1990
2000
2000

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(108 citation statements)
references
References 54 publications
(46 reference statements)
6
99
3
Order By: Relevance
“…cis-Acting sequences and trans-acting factors have been postulated to influence the alternative splicing pattern of CD45. Linker scanning analysis revealed that in exon A three segments (positions 8 -10, 40 -91, and 127-137, total length 198 bp) and in exon C one large segment (positions 16 -137, total length 144 bp) were essential for tissue-specific alternative splicing (46,47). No such segments were found in exon 5, suggesting that splicing of exon 5 is not regulated in a tissue-specific manner (46, 47).…”
Section: Discussionmentioning
confidence: 99%
“…cis-Acting sequences and trans-acting factors have been postulated to influence the alternative splicing pattern of CD45. Linker scanning analysis revealed that in exon A three segments (positions 8 -10, 40 -91, and 127-137, total length 198 bp) and in exon C one large segment (positions 16 -137, total length 144 bp) were essential for tissue-specific alternative splicing (46,47). No such segments were found in exon 5, suggesting that splicing of exon 5 is not regulated in a tissue-specific manner (46, 47).…”
Section: Discussionmentioning
confidence: 99%
“…NIH 3T3 cells, a MHC class II-negative B7-negative murine fibroblast cell line, were transfected by electroporation with DR7 (t-DR7), B7 (t-B7), or both DR7 and B7 (t-DR7/B7). For each transfection 20 .g of Pvu I-linearized plasmid containing the B7-pLEN construct (8) (a kind gift of California Biotechnology, Mountain View) and/or 20 ug each of the DRa and DRB1*0701 /-chain cDNAs (21) were transfected with 5 ,ug of Pvu I-linearized SV2-Neo-Sp65 plasmid (22). The expression of MHC class II and B7 molecules was assessed using mAbs 9-49 and anti-B7, respectively.…”
mentioning
confidence: 99%
“…The small Xba I-Dra III DNA fragment of the mutant CD26 cDNA containing the deletion was substituted for the corresponding DNA fragment of the wild-type CD26 cDNA in the expression vector RcSRa to yield RcSRa-26A3-9 (13). A mixture of RcSRa-26.A&3-9 and pMT-2 (14) providing the dihydrofolate reductase (DHFR) gene was used to transfect a DHFR-deficient CHO cell line, DXB-11, by electroporation (15).…”
mentioning
confidence: 99%